Nilotinib for the treatment of chronic myeloid leukemia: An evidence-based review - Jabbour, Elias (Dove Medical Press, 2010)
INTRODUCTION: Chronic myelogenous leukemia (CML) is a progressive and often fatal hematopoietic neoplasm. The Bcr-Abl tyrosine kinase inhibitor imatinib mesylate represented a major therapeutic advance over conventional CML therapy, with more than 90% of patients obtaining complete hematologic response, and 70%–80% of patients achieving a complete cytogenetic response. Despite the high efficacy of imatinib, a minority of patients in chronic phase CML and more patients in advanced phases are resistant to imatinib, or develop resistance during treatment. This is attributed, in 40% to 50% of cases, to the development of mutations in the Bcr-Abl tyrosine kinase domain that impair imatinib binding. Attempts to circumvent resistance led to the discovery of nilotinib (Tasigna), a novel, potent and selective oral Bcr-Abl kinase inhibitor. AIMS: To review the evidence for the use of nilotinib in the management of CML. EVIDENCE REVIEW: Preclinical and clinical investigations demonstrate that nilotinib effectively overcomes imatinib resistance, and has further improved the treatment of CML. PLACE IN THERAPY: Nilotinib is currently indicated for patients with CML in chronic and accelerated phases following imatinib failure. Randomized studies are ongoing to assess the efficacy of nilotinib in patients with newly diagnosed CML.